Carolingian Scholarship and Martianus Capella: The Oldest Commentary Tradition - Franz Fischer (RIDE, 2014)
This paper reviews a semi-diplomatic edition of the oldest gloss commentary on Martianus Capella's De nuptiis Philologiae et Mercurii, a popular fifth-century encyclopaedic allegory of the seven liberal arts. Based on and including facsimiles of a ninth-century manuscript from Leiden University Library (Vossianus Latinus Folio 48), the edition was produced collaboratively by various specialists. While it succeeds in providing full access to an important textual witness to a rich commentary tradition – the complex nature of which defies any attempts at capture in a print edition – the integration of a deeper critical analysis of the textual transmission and an augmentation of the material presented is still desirable.